APLIKASI TEKNOLOGI DIELECTRIC BARRIER DISCHARGE-UV PLASMA TERHADAP SIFAT FISIK DAN KIMIA TELUR AYAM (Gallus gallus domesticus) - Endrika Widyastuti; Aldila Daydeva (Universitas Tribhuwana Tunggadewi, 2018)
Eggs are food that contains high nutrition, however egg products susceptible damage so preservation process is required. Dielectric Barrier Discharge (DBD) UV Plasma has proven very effective as an alternative technology to preserve fresh egg by inactivation bacteria and prevent contamination in a fresh egg. the aim of this study is to evaluated effect of Dielectric Barrier Discharge (DBD) UV Plasma on physical and chemical quality of chicken eggs (Gallus gallus domesticus). The fresh eggs were stored at room temperature and assessed for their Physical (Haugh unit and yolk index) and chemical properties (yolk pH, albumen pH, and egg nutrition) on 0, 5, 7, 11, and 14 days. Analysis of variance (ANOVA) was used to analyze significant difference among the samples. The result shows that DBD UV plasma can maintain haugh unit, yolk index, yolk pH, and albumen pH than control. The eggs treated with DBD UV recorded have no significant difference for egg nutrition.